2014
DOI: 10.1002/chem.201403133
|View full text |Cite
|
Sign up to set email alerts
|

Electrofluorochromic Detection of Cyanide Anions Using a Nanoporous Polymer Electrode and the Detection Mechanism

Abstract: An electrofluorochromic (EFC) conjugated copolymer (PEFC) containing carbazole and benzothiadiazole (BTD) moieties is synthesized through Suzuki coupling followed by electrochemical polymerization, resulting in a nanoporous EFC polymer electrode. The electrode exhibits high sensitivity and selectivity in the EFC detection of cyanide anions (CN(-)) in largely aqueous electrolyte (67 vol % water) because electrochemical oxidation of PEFC leads to significant fluorescence quenching, and the presence of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Electrochemical oxidation, however, changed the film colour to black and quenched the fluorescence due to the formation of radical cations (polarons) and dications (bipolarons) along the conjugated polymer backbone [67]. Xu et al separately reported two carbazole-benzothiadiazole co-polymers P18a and 18b with both EC and EFC properties that were found useful for the detection of cyanide anions [68,69]. Nanoporous copolymer P18a exhibited an oxidative quenching with a high contrast ratio of 19.2 in the absence of cyanide anions [69].…”
Section: Elc Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical oxidation, however, changed the film colour to black and quenched the fluorescence due to the formation of radical cations (polarons) and dications (bipolarons) along the conjugated polymer backbone [67]. Xu et al separately reported two carbazole-benzothiadiazole co-polymers P18a and 18b with both EC and EFC properties that were found useful for the detection of cyanide anions [68,69]. Nanoporous copolymer P18a exhibited an oxidative quenching with a high contrast ratio of 19.2 in the absence of cyanide anions [69].…”
Section: Elc Polymersmentioning
confidence: 99%
“…Xu et al separately reported two carbazole-benzothiadiazole co-polymers P18a and 18b with both EC and EFC properties that were found useful for the detection of cyanide anions [68,69]. Nanoporous copolymer P18a exhibited an oxidative quenching with a high contrast ratio of 19.2 in the absence of cyanide anions [69]. Similarly, a thin film device of P18b spin-coated on ITO/poly(ethylene terephthalate) experienced up to 80% quenching of fluorescence upon undergoing electrochemical oxidation, due to the formation of carbazole radical cation and dications [68].…”
Section: Elc Polymersmentioning
confidence: 99%
“…The ELC layer can be deposited onto substrates by electropolymerization in a bath of electrolyte solution. For instance, X. Lu et al successfully prepared a nanoporous EFC copolymer film via electropolymerization . As shown in Figure a, in consecutive cyclic voltammograms, the oxidation and reduction current densities increased and their onsets decreased gradually with increasing cycle number.…”
Section: Elc Devicesmentioning
confidence: 99%
“…(a) Chemical structure of electropolymerized EFC copolymer, consecutive cyclic voltammograms for the electropolymerization and SEM images with different magnifications showing the surface morphology of the electropolymerized EFC film. Reproduced with permission . Copyright 2014, WILEY‐VCH.…”
Section: Elc Devicesmentioning
confidence: 99%
“…For example, ingested amygdalin, which is one of the most typical cyanogenic glycosides found in kernels such as peach, apricot, cherry and almond, would be hydrolysed by the widely distributed natural β-glucosidase and generated hydrogen cyanide (HCN) in living organisms, leading to disruption of normal physiological activities and may result in death caused by rapid suffocation 5 . Therefore, CN − monitoring has attracted much attention, and many techniques such as voltammetry, titrimetry, electrochemical and chromatography have been developed 6 7 8 9 10 . Unfortunately, most of these methods require expensive equipment and are complicated for real-time analyses.…”
mentioning
confidence: 99%